TEACHING COMPETENCIES OF UNDERGRADUATE STUDENTS IN EDUCATIONAL PRACTICE PROGRAM AS TEACHER CANDIDATES - Amri, Ariani; Djatmiko, Istanto Wahyu; Yuniarti, Nurhening; Triantini, Dewi; Wati, Miladiah Setio (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aimed to know the quality of undergraduate students’ teaching competencies as teacher candidates. The subjects of this study were 54 teachers of 32 vocational schools. The data was obtained from the Educational Practice Program (EPP) in Vocational High School (VHS) using online questionnaires via Google Form. This study used a quantitative descriptive approach with survey research. Data were analyzed using normality tests and product-moment correlation analysis. The results indicated that the undergraduate students’ competencies as candidate teachers were more dominant in social competency than personal, pedagogical, and professional competencies. Each competency had a highly strong relationship with others so that there was a significant attachment. Therefore, the undergraduate students as candidate teachers need to develop competencies to improve their quality in EPP. Abstrak: Penelitian ini bertujuan untuk mengetahui kualitas kompetensi mengajar mahasiswa sebagai calon guru. Subyek penelitian ini adalah 54 guru dari 32 Sekolah Menengah Kejuruan (SMK). Data diperoleh dari mata pelajaran pada Program Praktek Pendidikan di Sekolah Menengah Kejuruan (SMK) dengan menggunakan angket melalui Google Form. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan jenis penelitian survey. Data dianalisis menggunakan uji normalitas dan analisis korelasi product moment. Hasil penelitian menunjukkan bahwa kompetensi mahasiswa sebagai calon guru lebih dominan pada kompetensi sosial dibandingkan kompetensi kepribadian, pedagogik, dan profesional. Setiap kompetensi memiliki hubungan yang sangat kuat dengan yang lain sehingga terjadi keterikatan yang signifikan. Oleh karena itu, mahasiswa sebagai calon guru perlu meningkatkan kompetensi untuk meningkatkan kualitasnya di EPP.